Spinal cord infarction. A case report and narrative review - Pigna, Federica; Lana, Silvia; Bellini, Carlotta; Bonfanti, Laura; Creta, Michele; Cervellin, Gianfranco (Acta Biomedica Atenei Parmensis, 2021)
Spinal cord infarction is a rare but severe disorder, consistently less frequent than ischemic brain injury. It constitutes only 1-2% of all neurological vascular emergencies. Here we describe a case of spinal cord infarction in a 68-year-old Caucasian man without any neurological problem in his clinical history. The patient presented to the Emergency Department complaining for sudden onset of lower limbs weakness, as well as pain and mild loss of sensitivity in both legs. These symptoms suddenly arose after a 10 minutes bicycle race. He underwent a CT angiography, which confirmed the presence of a fusiform aneurysm of infra-renal abdominal aorta with thrombotic apposition on right lateral side and some ulcerated thrombi. As such, the patient underwent a spinal cord Magnetic Resonance Imaging, that showed images compatible with an acute ischemic injury (infarction) from D11 to medullary cone. He was then treated with low molecular weight heparin, aspirin, and methylprednisolone, and was then admitted to the Stroke Unit. He gradually regained lower limbs sensitivity totally, but the strength was only partially restored. Although a rare entity, Emergency Physicians should always keep in mind this possibility when evaluating patients with sudden loss of sensitivity and/or strength in their lower limbs.